INNOVATIVE APPROACHES TO COMPLETING INDEPENDENT GRAPHIC TASKS IN THE COURSE OF ENGINEERING AND COMPUTER GRAPHICS (Journal of Multidisciplinary Sciences and Innovations, 2025)
The article highlights the significance of teacher preparation, innovative pedagogical approaches, and the role of independent graphic tasks in teaching engineering and computer graphics. Methods for developing students’ graphic literacy, stages of evaluating independent work, and methodological strategies in the educational process are examined. In particular, the organization and assessment of students’ independent graphic assignments are scientifically justified.